2020
DOI: 10.3390/antibiotics9060362
|View full text |Cite
|
Sign up to set email alerts
|

N-Nonyloxypentyl-l-Deoxynojirimycin Inhibits Growth, Biofilm Formation and Virulence Factors Expression of Staphylococcus aureus

Abstract: Staphylococcus aureus is one of the major causes of hospital- and community-associated bacterial infections throughout the world, which are difficult to treat due to the rising number of drug-resistant strains. New molecules displaying potent activity against this bacterium are urgently needed. In this study, d- and l-deoxynojirimycin (DNJ) and a small library of their N-alkyl derivatives were screened against S. aureus ATCC 29213, with the aim to identify novel candidates with inhibitory potential. Among them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 82 publications
0
23
0
Order By: Relevance
“…In the subsequent ketalization step of OH groups in 10 , we used an alternative procedure to the standard protocol (PTSA, 2,2-dimethoxypropane, 2-methoxypropene) [ 48 ], in order to avoid strictly anhydrous conditions, which are typically required to limit by-product formation derived from acid-catalysed oxirane ring opening. Exploiting our longstanding expertise in the field [ 23 , 49 , 50 , 51 , 52 , 53 ], we chose the procedure involving the use of polymer-supported triphenyl phosphine (PS-TPP)/I 2 /imidazole (ImH) system as the activating agent for the protection reaction, using acetone as the acetonide source. In this case, the reaction involves the activation of acetone by the triphenylphosphonium iodide and the subsequent double attack by the diol to the activated ketone.…”
Section: Resultsmentioning
confidence: 99%
“…In the subsequent ketalization step of OH groups in 10 , we used an alternative procedure to the standard protocol (PTSA, 2,2-dimethoxypropane, 2-methoxypropene) [ 48 ], in order to avoid strictly anhydrous conditions, which are typically required to limit by-product formation derived from acid-catalysed oxirane ring opening. Exploiting our longstanding expertise in the field [ 23 , 49 , 50 , 51 , 52 , 53 ], we chose the procedure involving the use of polymer-supported triphenyl phosphine (PS-TPP)/I 2 /imidazole (ImH) system as the activating agent for the protection reaction, using acetone as the acetonide source. In this case, the reaction involves the activation of acetone by the triphenylphosphonium iodide and the subsequent double attack by the diol to the activated ketone.…”
Section: Resultsmentioning
confidence: 99%
“…Escober et al demonstrated that the nuclear factor-kappa B inhibitor N-[3,5-Bis(trifluoromethyl) phenyl]-5-chloro-2-hydroxybenzamide at sub-MIC of 0.0313 μg/mL can inhibit the initial cell attachment and biofilm formation of vancomycin-resistant S. aureus strain VRS1 in a dose-dependent manner [68] . The sub-MICs of other antimicrobial compounds, such as N-nonyloxypentyl-L-DNJ, N4-benzyl-N-2-phenylquinazoline-2,4-diamine, terpenoid (+)-nootkatone, chitosan, marine steroid siphonocholin, zinc oxide, and silver nanoparticles, are found to be able to inhibit the biofilm formation of diverse S. aureus strains [43] , [46] , [69] , [70] , [71] , [89] .…”
Section: Effects Of Sub-mics Of Antibiotics On S Aureus Biofilm Formationmentioning
confidence: 99%
“…Recently, as part of our longstanding research program that focused on the analysis of the effect of sugar chirality in the biological properties of iminosugars [ 15 , 22 , 23 , 24 ] and other enantiomeric bioactive compounds [ 25 , 26 , 27 , 28 ], we evaluated the antimicrobial potential of d - and l -DNJ, as well as that of a small library of their N -alkyl derivatives, against Staphylococcus aureus ATCC 29,213 [ 29 ]. Our data recognize a role of the lipophilicity of iminosugars in contributing to their antibacterial activity against S. aureus more evidently for the l -enantiomers.…”
Section: Introductionmentioning
confidence: 99%
“…Our data recognize a role of the lipophilicity of iminosugars in contributing to their antibacterial activity against S. aureus more evidently for the l -enantiomers. This led to the identification of N -nonyloxypentyl- l -DNJ ( l -NPDNJ, ent - 9 Figure 3 ) as an interesting candidate, because of its capacity to affect growth, biofilm formation and virulence factor expression of S. aureus [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation